Orthogonal Activation of Metabotropic Glutamate Receptor Using Coordination Chemogenetics - Senoo, Akinobu; Yamada, Yutaro; Ojima, Kento; Doura, Tomohiro; Hamachi, Itaru; Kiyonaka, Shigeki (Frontiers in Chemistry, 2022)
Cell-surface receptors play a pivotal role as transducers of extracellular input. Although different cell types express the same receptor, the physiological roles of the receptor are highly dependent on cell type. To understand each role, tactics for cell-specific activation of the target receptor are in high demand. Herein, we developed an orthogonal activation method targeting metabotropic glutamate receptor 1 (mGlu1), a G-protein coupled receptor. In this method, direct activation via coordination-based chemogenetics (dA-CBC) was adopted, where activation of mGlu1 was artificially induced by a protein conformational change in response to the coordination of a metal ion or metal-ion complex. Our structure-based protein design and screening approach identified mGlu1 mutants that were directly activated by the coordination of Cu2+ or Zn2+, in addition to our previous Pd-complex-sensitive mGlu1 mutant. Notably, the activation of the mutants was mutually orthogonal, resulting in cell-type selective activation in a model system using HEK293 cells.